Most significant change in the Cordilleras: A pilot evaluation. - International Potato Center (Department of Agriculture, 2018)
This book presents the Most Significant Change story (MSC) in the Agriculture, agribusiness, and income generating activities (AAIGA) component of CHARMP2 (second Cordillera Highland Agricultural Resource Management Project); as well as the selected stories from the provinces. The second part of this book includes an MSC process review, learnings, and recommendations.